X‐ray phase contrast tomography for the investigation of amyotrophic lateral sclerosis. (9th June 2020) - Begani Provinciali, Ginevra; Pieroni, Nicola; Bukreeva, Inna; Fratini, Michela; Massimi, Lorenzo; Maugeri, Laura; Palermo, Francesca; Bardelli, Fabrizio; Mittone, Alberto; Bravin, Alberto; Gigli, Giuseppe; Gentile, Francesco; et al.
Abstract : Ex vivo X‐ray phase contrast tomography of amyotrophic lateral sclerosis of a SOD1 G93A mouse model is presented. Quantification of neuronal and vascular alteration in the central nervous system is described. Abstract : Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder affecting motor neurons. Pre‐clinical studies drive the development of animal models that well mimic ALS disorder and enable both the dissection of disease processes and an early assessment of therapy efficacy. A comprehensive knowledge of neuronal and vascular lesions in the brain and spinal cord is an essential factor to understand the development of the disease. Spatial resolution and bidimensional imaging are important drawbacks limiting current neuroimaging tools, while neuropathology relies on protocols that may alter tissue chemistry and structure. In contrast, recent ex vivo studies in mice demonstrated that X‐ray phase‐contrast tomography enables study of the 3D distribution of both vasculature and neuronal networks, without sample sectioning or use of staining. Here we present our findings on ex vivo SOD1 G93A ALS mice spinal cord at a micrometric scale. An unprecedented direct quantification of neuro‐vascular alterations at different stages of the disease is shown.